Singapore as a sustainable city: Past, present and the future - FUJII, Tomoki (Institutional Knowledge at Singapore Management University, 2019)
This paper outlines Singapore’s major sustainability challenges and its policy response in the areas of land use, transportation, waste management, water, and energy. We review the current and past Concept Plans from the perspective of sustainable land use and provide an overview of transportation policy in Singapore. We also examine Singapore’s policies to manage increasing wastes and review the four tap water management plan. Finally, we look at various initiatives by the government for sustainable use of energy. While Singapore has been successful in many ways in transforming itself into one of the most prosperous and sustainable cities in the world, there remain challenges to make the city even cleaner and greener for a better future. We discuss the opportunities that new technologies will bring about and the role that Singapore can play in building a sustainable city.